Pendampingan Penerapan Strategi Pemasaran Produk di Desa Pandahan Kecamatan Bati-Bati Tanah Laut (Usaha Sayur Hidroponik) - Vitria, Aida; A, Abdurrahim; P, Purboyo; H, Ana Sofia; GA, Gt Meinar; Wahyuni, Amalia (Yayasan Daarul Huda Kruengmane, 2024)
Hydroponics vegetables have become an increasingly popular choice for consumers who care about health and the environment. This agricultural method offers a large amount of advantages, including cleaner production, more efficient water use, and more hygienic and healthy crop results and without using the soil, but rather using the rich nutritional solution to plant growth. However, the problem faced is that there are many strict competitors from other hydroponics farmers, so they are very much needed marketing strategies so that products can always be in markets/society, have high competitiveness. The implementation method on this extension is the identification of needs, preparation of counseling material, extension, and assistance.The results of this extension are after participating in counseling activities, participants realize that the application of a marketing strategy can help them to face competition and be able to compete, create the added value of the product, and expand market share. Participants also share experiences with the obstacles in implementing the marketing strategy of these hydroponics products, for example, are still limited capital, lack of knowledge of marketing sciences, and dealing with competition.This advice from extension is expected that this activity can provide maximum benefits, it is also recommended to local governments, to provide further and continuous support to hydroponic vegetable business actors, especially on the implementation of its marketing strategy. Support in the form of advanced training can be related to implementing marketing strategies to the use of marketing access, assistance programs to further develop the marketing of hydroponics vegetable products. And similar activities are expected to be sustainable so that the business of hydroponics vegetables can increase its visibility and achieve success in the pemasarn products.